Bi-directional Relationship between Periodontitis and Systemic Diseases - Tanwir, Farzeen; Wasif Haq , Muhammad; Tabassum, Saba; Hafeez, Nabeel; Faraz Siddiqui , Mohammad; Mazhar , Saima; Bibi, Tauqeer; Mehwish, Ayesha; Zaidi, Natasha; Khalid Khan, Ahmed Bin; Nawaz, Madiha; Baqar, Anum; et al. (Research Highlights in Disease and Health Research Vol. 4, 2023)
This chapter aims to determine the frequency of periodontitis in patients with systemic diseases admitted in the hospital. There are 450 patients in this cross-sectional study. The information was gathered from Pakistan Institute of Medical Sciences, Capital Development Authority, Islamic International Dental College, Islamabad and Jinnah Postgraduate Medical Center, Karachi. The patients in the study were suffering from diseases such as diabetes mellitus, cardiovascular disorders (with and without diabetes mellitus), respiratory disorders, gastrointestinal disorders, hepatic disorders, renal disorders, bone/joint disorders and hypertension. With the aid of a sterile dental mirror, periodontal probe, wooden tongue depressor, and torch, the condition of the periodontium was evaluated. The following systemic diseases have a negative impact on periodontal status and are listed in descending order of severity: Diabetes mellitus+cardiovascular disease> Diabetes mellitus> Cardiovascular disease> Bone/joint disorders> Renal p roblems> Hypertension> Hepatic disease> Gastrointestinal disorders> Respiratory problems. In terms of periodontitis, 37% of population experienced mild periodontitis, 28% had aggressive periodontitis, 27% had moderate periodontitis while 8% had gingivitis. The results of the study indicate the bidirectional relationship between Periodontitis and systemic diseases and development of severe periodontitis. This means Oral health is closely related to systemic health which implies that improvement of oral health can lead to betterment of the systemic health which will lead to better quality of life for the patient. Therefore we recommend collaboration between dentists and medical physicians through which focus on prevention and treatment of oral as well as systemic health can be achieved. Optimization of patients’ health is the goal of both the medical and dental professions.